E-SAMSAT: SARANA UNTUK MEMBANTU DAN MEMUDAHKAN WAJIB PAJAK MELAKUKAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR - Rina Rindiyani; Moh. Faisol (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2023)
The aims of this reseach to know the implementation of E-Samsat at the Sumenep District SAMSAT Office. The researcher uses the case study method by conducting interviews with five informants: one SAMSAT office employee and four motor vehicle taxpayers who use E-Samsat. To analyze the data using qualitative data analysis (Miles & Huberman). The results of this study state that the implementation of the use of E-Samsat is very helpful and makes it easier for taxpayers to make motor vehicle tax payments. Taxpayers don't need to stand in long queues, because they can make tax payments from anywhere, and at any time via E-Samsat. However, the biggest contribution to accessing E-Samsat is the internet network, so whether or not the network is stable affects the utilization of E-Samsat.